The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1016/j.atherosclerosis.2012.05.023
|View full text |Cite
|
Sign up to set email alerts
|

Plaque characteristics and arterial remodeling in coronary and peripheral arterial systems

Abstract: Background Few studies have examined plaque characteristics among multiple arterial beds in vivo. The purpose of this study was to compare the plaque morphology and arterial remodeling between coronary and peripheral arteries using gray-scale and radiofrequency intravascular ultrasound (IVUS) at clinical presentation. Methods and Results IVUS imaging was performed in 68 patients with coronary and 93 with peripheral artery lesions (29 carotid, 50 renal, and 14 iliac arteries). Plaques were classified as fibro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
45
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 30 publications
(35 reference statements)
0
45
0
Order By: Relevance
“…2,14,23 Matsuo et al investigated plaque characteristics and arterial remodeling using intravascular ultrasonography in coronary and peripheral arteries such as the carotid, renal, and iliac arteries, and reported that arteries with ER, compared with those with negative remodeling, demonstrated more characteristics of fibroatheroma, which is one of the most significant features of vulnerable plaque regardless of its location. 20 There have been 2 previous studies that used multidetector CT angiography to investigate the association between ER in the CA and clinical presentation. 13,21 The purpose of this study was to assess the feasibility of longaxis CA MRI 33 for quantitative assessment of ER and to evaluate the association between the extent of ER and cerebral ischemic events.…”
mentioning
confidence: 99%
“…2,14,23 Matsuo et al investigated plaque characteristics and arterial remodeling using intravascular ultrasonography in coronary and peripheral arteries such as the carotid, renal, and iliac arteries, and reported that arteries with ER, compared with those with negative remodeling, demonstrated more characteristics of fibroatheroma, which is one of the most significant features of vulnerable plaque regardless of its location. 20 There have been 2 previous studies that used multidetector CT angiography to investigate the association between ER in the CA and clinical presentation. 13,21 The purpose of this study was to assess the feasibility of longaxis CA MRI 33 for quantitative assessment of ER and to evaluate the association between the extent of ER and cerebral ischemic events.…”
mentioning
confidence: 99%
“…Following angiography, greyscale and VH-IVUS were performed using phased-array 20 MHz IVUS catheters and the S5 Imaging System (Eagle-Eye Gold, Volcano Corporation, Rancho Cordova, California) in the left anterior descending artery (LAD), [8, 12, 1921]. The image examination was performed by a blinded observer in the IVUS Imaging center at Mayo Clinic, Rochester.…”
Section: Methodsmentioning
confidence: 99%
“…16,18 One of the most often studied findings associated with plaque vulnerability is arterial remodeling. Initially described by Glagov et al 19 in 1987, the positive arterial remodeling has been observed in atherosclerotic plaques responsible for acute coronary events, 6,20,21 and is associated with the increase in CK-MB after PCI, 22 no-reflow phenomena during primary PCI, 23 recurrent ischemia after PCI, 24 major cardiovascular events in patients with unstable angina undergoing any form of revascularization, 25 and intimal hyperplasia after PCI with bare-metal 26 and drug-eluting stents. 27 In the present study, the mean arterial-remodeling index was 1.4 ± 1.0, greater than 1.05, thus characterizing the predominance of positive arterial remodeling and corroborating the aforementioned literature.…”
Section: Discussionmentioning
confidence: 99%
“…4,5 The IVUS identifies plaque and calcium nodule rupture with high sensitivity and specificity. Additionally, several findings at IVUS are characteristic of unstable plaques, such as extensive positive remodeling 6 and the presence of small amounts of calcium with localized and scattered distribution (spotty calcification). 7,8 Recently, the application of tissue characterization with the iMAP™ technology (Boston Scientific, Santa Clara, United States) made further progress in the identification of atherosclerotic plaque composition, identifying and quantifying the lipidic and necrotic contents, which are directly related to lesion instability.…”
mentioning
confidence: 99%